PENGARUH STRUKTUR KEPEMILIKAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL (CSR DISCLOSURE) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Efva Donata Ghozali (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2014)
The purpose of this study was to examine the effect of ownership structure in terms of ownership and management of institutional ownership and company characteristics in terms of industry type and company size on disclosure of corporate social responsibility (CSR Disclosure) on companies listed on the Indonesia Stock Exchange (IDX) the period 2007-2009. Sample selection method used is Purposive Sampling of companies listed on the Indonesia Stock Exchange (BEI), in order to obtain a sample of 189 companies. Testing method used in this study was multiple linear regression model. The results of this study prove that the disclosure of corporate social responsibility (CSR Disclosure) is affected by ownership structure in terms of management ownership, institutional ownership and company characteristics in terms of industry type and company size.